(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Edentulism is a sequel of tooth loss that leads to impairment of function, comfort, esthetics and speech. Kennedy’s classification is a common classification used to classify partial edentulism and It helps to understand edentulism in a defined manner. The partial edentulism patients may have physical variations and health that differ for each individual.Aim: The aims of this study to evaluate the prevalence of Kennedy’s Class IV classification based on gender and arch.Materials and Methods: A retrospective study was conducted among patients visiting Saveetha Dental College and data were retrieved from Dental Information Archiving Software (DIAS). Parameters were assessed including gender and arches of Kennedy’s Class IV classification. Data were collected and tabulated in Microsoft Excel sheets and Statistical analysis was done using SPSS Software. The association between study variables was calculated using the Chi-Square test, where p<0.05 was considered statistically significant.Results: In this study, a total of 96 patients with partial edentulism of Kennedy’s Class IV are more common in males (60.4%) than females and the most common arch was found to be mandibular arch (50.1%). There is no significant difference between the gender and arches for patients with Kennedy’s Class IV partial edentulism (p>0.05). Hence, statistically not significant.Conclusion: Within the limits of this study, this study showed that the prevalence of Class IV Kennedy’s classification of partial edentulous, male patients is most affected and the lower arch is being the most common arch.